Improving the Labour Costs Efficiency at Ukrainian Enterprises - Olga Sukach (CES Working Papers, 2014)
Generally, labor costs are more complicated than other inputs. But wages and labor productivity in Ukraine are significantly lower than in the market economies. Also the share of the basic wages consisted by 61.1 per cent at Ukrainian enterprises. While, the developed countries keep a basic wage at the rate of about 80-85 per cent. Consequently, wage is transformed into one of the version of a social assistance, which in less degree dependents on the results. The main purpose of the article is a theoretical studied of a system of economic indicators of labor costs efficiency and a critical analysis of their calculations in Ukrainian enterprises and abroad. In support of correlation between the share of basic wages and labor productivity the multiplicative model of labor productivity is developed and was practically used by the author on one of Ukrainian enterprises.
Keywords: M52; J31; E22; C38; 330; remuneration of labor; payroll; labor costs; labor productivity; own-product real wage